UJI EFEKTIVITAS BEBERAPA MEDIA UNTUK PERBANYAKAN AGENS HAYATI Gliocladium sp. - Gusnawaty, HS; Taufik, Muhammad; Wahyudin, Edi (Jurnal Agroteknos, 2013)
This research was carried out in the Laboratory of Pests and Disease, Agricultural Faculty  of  Haluoleo  University,  from  October  to  December  2012.  This  research  was arranged   in   A   Completely   Randomized   Design   (CRD),   with   7   treatments,   namely: Gliocladium sp. in sago waste (a), Gliocladium sp. in cashew seed wastes (b), gliocladium sp. in saw dust waste (c), Gliocladium sp. in corn medium (d), Gliocladium sp. in bran medium (e),  Gliocladium  sp.  in rice  medium  (f) and  gliocladium sp.  in rice  husk  waste  (g).   The research results showed that media used had different effectiveness.   The most effective medium for Gliocladium sp. Propagation was rice bran medium, based on Gliocladium sp. growth (100%), and the number of Gliocladium sp. conidium ( 2,0 x105/g). Keywords: effectiveness, Gliocladium sp., medium, propagation